Role of the Antioxidant Activity of Melatonin in Myocardial Ischemia-Reperfusion Injury - Jorge Luis Bermudez-Gonzalez; Denya Sanchez-Quintero; Leonardo Proaño-Bernal; Rafael Santana-Apreza; Marco Antonio Jimenez-Chavarria; Jose Antonio Luna-A; Juan Ignacio Straface; Arantza Marie Perez-Partida; Joaquin Berarducci; Javier Ivan Armenta-Moreno; Karla Joana Garza-Cruz; Nilda Espinola-Zavaleta; et al. (MDPI AG, 2022)
Ischemia-reperfusion injury is a common problem in the age of interventional cardiology; it is primarily mediated by oxidative stress and reactive agents. Melatonin has antioxidative properties that make its use promising for treating ischemia-reperfusion injury. Multiple experimental studies in murine and porcine models have been performed with good results. Clinical trials have also been conducted but given their heterogeneity, no conclusive results can be made. Melatonin pharmacokinetic properties are not ideal; therefore, many analogs have been proposed with improved characteristics, and some studies have evaluated their efficacy in animal models, but clinical trials are needed to recommend their use. In this review, we expose the results of the most impactful studies regarding melatonin use in ischemia-reperfusion injury.